2015
DOI: 10.1016/j.susc.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the NiFe2O4(001) surface in contact with gaseous O2 and water vapor

Abstract: Nickel ferrite, NiFe 2 O 4 , is a material with interesting physical properties and useful technological applications. We have used Density-functional theory with on-site Coulomb repulsion U term to study the structure, electronic properties, and energetics of the NiFe 2 O 4 (001) surface and its interaction with water both in the absence and in the presence of surface oxygen vacancies. In a humid environment, water adsorbs dissociatively on the surface oxygen vacancies leading to the formation of surface hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…The Coulomb repulsions of 3d states of Ni and Fe were taken into account as the reference. 52 Spin polarization and magnetic properties were considered as well. 53 We used the most preferable surface (111) of nickel ferrite spinel, which has been reported by previous theoretical studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Coulomb repulsions of 3d states of Ni and Fe were taken into account as the reference. 52 Spin polarization and magnetic properties were considered as well. 53 We used the most preferable surface (111) of nickel ferrite spinel, which has been reported by previous theoretical studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We chose a plane-wave energy cutoff of 400 eV with the residual force components on each atom lower than ∼0.05 eV Å –1 atom –1 . The Coulomb repulsions of 3d states of Ni and Fe were taken into account as the reference . Spin polarization and magnetic properties were considered as well …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The structure, electronic properties, and energetics of the NiFe 2 O 4 ð001Þ surface and its interaction with water both in the absence and in the presence of surface oxygen vacancies have been studied using DFT+U. 122 It was shown that water adsorbs dissociatively on the surface oxygen vacancies leading to the formation of surface hydroxyls. Furthermore, it was found that at high temperature, water desorbs leaving a surface containing oxygen vacancies.…”
Section: Surfaces and Adsorptionmentioning
confidence: 99%
“…Surfaces with V O s are favoured, and these react with water to create adsorbed hydroxyls in a humid atmosphere. Reprinted from ref [533],. with permission from Elsevier.…”
mentioning
confidence: 99%